Capacity Building in Waste to Wealth: Reusing of Discarded Tyres for Making Household Furnitures - Oyinloye, Michael Abiodun; Siyanbola, Afeez Babatunde; Uzzi, Festus O. (NIU Journal of Humanities, 2020)
This paper discussed capacity building and its relevance in the transformation of waste to wealth. The study enunciated that capacity building strategies in waste to wealth are anchored on harnessing creative skills for stimulating entrepreneurial opportunities. It emphasized that entrepreneurial ideas in the areas of waste to wealth contribute immensely to the economic growth of developing countries to create sustainable jobs. The paper noted that reusing tyres and other was items is more environmentally sustainable that recycling processes which pollutes the environment. However, the researchers skillfully reused discarded tyres in producing household furniture. Foam and Adire fabric was utilized as cover for the produced furniture for usability and attractiveness. Metal stands were affixed underneath the furniture to achieve balance and durability. The produced furniture is suitable for homes and public use. Keyword: Capacity-Building   Entrepreneurship   Waste management     Reuse